Faktor-Faktor Yang Mempengaruhi Good Governance dengan Sumber Daya Manusia sebagai Variabel Moderasi - Sally Edinov; Taufeni Taufik; Yesi Mutia Basri; Novita Indrawati; Emrinaldi Nur DP (Politeknik Ganesha Medan, 2022)
This study aims to find the empirical evidence of the influence about the Government's of Internal Control System, Fixed Assets Administration, Organizational Culture, Organizational Commitment and Information Technology on Good Governance with Human Resources as the moderating variable. This research was conducted in the work unit of Directorate General of Natural Resources and Ecosystem Conservation, the Ministry of Environment and Forestry. The sampling technique used is the census d method by sending a questionnaire to the Nation Civil Apparatus using the application of Financial Accounting System at the agency level. Of the 225 questionnaires distributed, 218 were processed using WarpPLS 7.0 analysis. The results of the study prove that there is an influence of the Government's Internal Control System and Fixed Assets Administration on Good Governance. Meanwhile, Organizational Culture, Organizational Commitment and Information Technology cannot affect Good Governance. Human Resources are only able to moderate the relationship between the Government's Internal Control System and Fixed Assets Administration with Good Governance but are not able to moderate the relationship between Organizational Culture, Organizational Commitment, Information Technology and Good Governance.